Carbon isotope ratios of Great Plains soils and in wheat-fallow systems - Peterson, G. A., author; Lyon, D., author; Halvorson, A. D., author; Leavitt, S. W., author; Paul, Eldor A., author; Follett, R. F., author; Soil Science Society of America, publisher (Colorado State University. Libraries, 1997)
The purposes of this study were to improve knowledge of regional vegetation patterns of C3 and C4 plants in the North American Great Plains and to use δ13C methodology and long-term research sites to determine contributions of small-grain crops to total soil organic carbon (SOC) now present. Archived and recent soil samples were used. Detailed soil sampling was in 1993 at long-term sites near Akron, CO, and Sidney, NE. After soil sieving, drying, and deliming, SOC and δ13C were determined using an automated C/N analyzer interfaced to an isotope-ratio mass spectrometer. Yield records from long-term experimental sites were used to estimate the amount of C3 plant residue C returned to the soil. Results from δ13C analyses of soils from near Waldheim, Saskatchewan, to Big Springs, TX, showed a strong north to south decrease in SOC derived from C3 plants and a corresponding increase from C4 plants. The δ13C analyses gave evidence that C3 plant residue C (possibly from shrubs) is increasing at the Big Springs, TX, and Lawton, OK, sites. Also, δ13C analyses of subsoil and topsoil layers shows evidence of a regional shift to more C3 species, possibly because of a cooler climate during the past few hundreds to thousands of years. Data from long-term research sites indicate that the efficiency of incorporation of small-grain crop residue C was about 5.4% during 84 year at Akron, CO, and about 10.5% during 20 year at Sidney, NE. The 14C age of the SOC at 0- to 10-cm depth was 193 year and at 30 to 45 cm was 4000 yr; 14C age of nonhydrolyzable C was 2000 and 7000 year for these same two respective depths. Natural partitioning of the 13C isotope by the photosynthetic pathways of C3 and C4 plants provides a potentially powerful tool to study SOC dynamics at both regional and local scales.
Keywords: SOM; 13C isotope; isotopic shift; grasses